Financial market data for international financial stability - Davies, E. Philip; Hamilton, Robert; Heath, Robert; Mackie, F.; Narain, A.; Centre for Central Banking Studies, Bank of England (London Bank of England, 1999)
This report contributes to the debate about financial market data for international financial stability in four ways: by setting out a list of data series identified by users of data as being needed for the monitoring of international financial stability; by examining existing frameworks to see the extent these meet data requirements; establishing the gaps in these frameworks and how they might be filled; and investigating specific issues relating to banking indicators and to the measurement of repurchase agreement and derivative activity. Issues such as why and how financial instability occurs are explored in the "Lecture Series" attachment.
Includes bibliographical references
osc 05/08/16
Loans
Keywords: Financial Market; Risk management; International finance; Capital movements; Disclosure of information; Taxation; Finance; Economics